Toe-out gait decreases knee load during stair descent in healthy individuals - Rui Tsukagoshi; Riho Honda; Haruka Senoo; Mika Goto; Yuki Hashimoto; Akira Yamanaka (Elsevier, 2021)
Introduction: Both toe-out (TO) and toe-in (TI) gaits decrease knee load during walking and stair ascent. However, few reports have focused on stair descent, which requires a higher load compared with walking. Objectives: The purpose of this study was to investigate the effect of foot progression angle (FPA) on knee joint load and related variables during stair descent. Methods: Twenty-two healthy young adults performed a stair descent task at a predefined speed of 90 steps/min with normal gait, TO gait (15° > normal), and TI gait (15° < normal). 3D motion analysis was conducted. In addition, the ground reaction force (GRF) with 3 components, center of pressure (COP) positions, and sagittal and frontal plane hip and knee joint kinematic and kinetic variables were recorded during stair descent. Results: The medial GRF increased, and the COP position was more lateral in TO gait compared with normal and TI gait during stair descent. TO gait exhibited a significant decrease in the peak knee adduction moment by ∼20% compared with normal gait and by ∼23% compared with TI gait. In addition, the knee flexion moment in TI gait significantly increased compared with normal and TO gait. Conclusions: TO gait decreases knee joint load during stair descent. Our results might have important implications for patients with knee osteoarthritis (OA) or those at risk of developing knee OA. Moreover, it will be of great interest to those involved in the research or clinical practice dealing with the role of gait in pathologic conditions, such as OA.